Oxidative stress during hypoxic training and the mechanism behind hypoxic acclimatization - Huang, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The effect that oxidative stress has on myocardial mitochondria in rats during intermittent hypoxic training was examined. The mechanism of hypoxic acclimatization of mitochondrial was also explored in order to provide a theoretical basis for the use of hypoxic training. Methods Sprague-Dawley rats were involved in acute and chronic training at altitudes of 3000m and 4000m. Myocardial mitochondrial ultrastructure, ROS, MDA, ATP and free Ca2+, as well as SOD and GSH-Px activity and their gene expression were assessed. Results The myocardial ultrastructure was damaged by acute hypoxic stress, and the damage at 4000m was more severe than that incurred at 3000m. The damage included decreases in the electron density of ground substances, coagulation of mitochondria and disorder and blurring of mitochondrial cristae. A decrease of heterochromatin in the nuclei was also observed. ROS and MDA increased during hypoxic stress, and furthermore, ATP and free Ca2+, as well as SOD and GSH-Px activity and their gene expression decreased. After 4-weeks of hypoxic acclimatization at an altitude of 3000m, ROS and MDA decreased, ATP and free Ca2+ increased, and SOD,and GSH-Px activity and their gene expression also increased. The damage to the myocardial ultrastructure in the rats at 3000m was found to be reversible, however at 4000m the damage was not reversible. Conclusions Hypoxic exercise decreased the efficiency of oxidative phosphorylation and ATP production, while increasing free radical production, causing damage to the mitochondrial structure and injuring the function of the myocardial cell. The injury incurred at 4000m was more severe than that at 3000m. After a 4-week training program and hypoxic acclimatization, the function of mitochondria in the 3000m group had been recovered, but only partial improvement was seen in the group trained at 4000m. The results indicate that the damage of the myocardial cell is likely to be reversible in rats trained at an altitude of 3000m but the damage at 4000m is irreversible.